If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -1(-4) = x Multiply -1 * -4 15 + 4 = x Combine like terms: 15 + 4 = 19 19 = x Solving 19 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 19 + -1x = x + -1x Combine like terms: x + -1x = 0 19 + -1x = 0 Add '-19' to each side of the equation. 19 + -19 + -1x = 0 + -19 Combine like terms: 19 + -19 = 0 0 + -1x = 0 + -19 -1x = 0 + -19 Combine like terms: 0 + -19 = -19 -1x = -19 Divide each side by '-1'. x = 19 Simplifying x = 19
| 6(2x-9)=4+11x | | 18/7.5=x/5 | | 3x-y+z=1 | | -3x-5=6x-32 | | 13=2y-3y+4 | | 5x^2-10x-80=0 | | 2(w-3)=3(w-1) | | 7k^2-6k*3=3 | | 32/4=b+4/3 | | 80+6x=145+7x | | 8=8n-4(a+8) | | .125d+7=16 | | 16a^2+24a+9= | | 2x-3y+z=-3 | | -3x^2+11x+25=0 | | 2x-1+6x=28 | | y=2x(4+3)-2 | | -11+z=6(z-4) | | 9v^2-121f^2= | | -7-2x-x=2 | | -6(1+3k)=-36-3k | | 2x^2-30x+75=0 | | x+6+2x=-x-4-2 | | 10p+4=-3+7p+1p | | -6(2x-3)+15=36 | | 9a^2+42at+49t^2= | | 5t+4=5+4t | | -6(2x-3)+15=33 | | -3(p+3)=-2(-2p-3)-2p | | [2x-7]=3 | | -2y+5x=12 | | 28n^2-96=-184n |